2003
DOI: 10.4025/actascibiolsci.v25i1.2075
|View full text |Cite
|
Sign up to set email alerts
|

Parasitóides coletados de fezes bovinas artificiais expostas em diferentes períodos de tempo em Itumbiara, Goiás, Brasil

Abstract: ABSTRACT. Parasitoids were collected from artificial bovine dung pats exposed for different periods of time in pasture from January to October 2001 in Itumbiara, Goiás, Brazil. Cattle dung pats were exposed in pastures for periods of 24, 48, 72, 96, 120, 144, 168, 192, 216, and 140h and were, then individually taken to the laboratory for parasitoids extraction. A total of 100 dung pats were exposed in the pasture and 430 parasitoid individuals were recovered from them. The most abundant species extracted were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Estes resultados diferem do padrão apresentado pela fauna de Scarabaeinae coletada em áreas abertas em distintas localidades do Brasil (por exemplo, Flechtmann et al 1995, Aidar et al 2000, Koller et al 1999, Marchiori 2000, 2003, onde frequentemente há um número maior de espécies paracoprídeas em relação às demais guildas, como encontrado por Halffter et al (1992) e Louzada & Lopes (1996) para áreas de floresta Neotropical. Este fato possivelmente se deve ao maior número de espécies pertencentes à Deltochilini que ocupam áreas abertas nesta região, onde as espécies escavadoras parecem mais restritas a habitats florestais.…”
Section: Discussionunclassified
“…Estes resultados diferem do padrão apresentado pela fauna de Scarabaeinae coletada em áreas abertas em distintas localidades do Brasil (por exemplo, Flechtmann et al 1995, Aidar et al 2000, Koller et al 1999, Marchiori 2000, 2003, onde frequentemente há um número maior de espécies paracoprídeas em relação às demais guildas, como encontrado por Halffter et al (1992) e Louzada & Lopes (1996) para áreas de floresta Neotropical. Este fato possivelmente se deve ao maior número de espécies pertencentes à Deltochilini que ocupam áreas abertas nesta região, onde as espécies escavadoras parecem mais restritas a habitats florestais.…”
Section: Discussionunclassified
“…While such a limited number of rearing records may be seen as weak evidence for host specificity, numerous other studies have reared parasitoids from dipteran puparia in the neotropics, and none of these have yielded C. annulifera. A review of 18 studies in Argentina, Brazil, Mexico, the Dominican Republic, and Peru revealed no evidence of C. annulifera being reared from at least 24 species of tephritid, muscid and sarcophagid Diptera (Diaz et al 1996, Mendes and Linhares 1999, Ovruski et al 2005, Marchiori et al 2002, Aguiar-Menezes et al 2004, Garcia and Corseuil, 2004, Geden et al 2006, Hern andez-Ortiz et al 2006, Marchiori 2006, Marchiori and Silva Filho 2007, Loera-Gallardo et al 2008, Romero et al 2010, Batt an Horenstein and Salvo 2012, Avila-Rodr ıguez et al 2015, Taveras and Hansson 2015, Montoya et al 2016). These studies did, however, yield 31 other pupal parasitoid species, including the well-known dipteran generalists Nasonia vitripennis (Walker), Muscidifurax raptor (Girault and Sanders), Spalangia endius (Walker) (all Pteromalidae), and Brachymeria podagrica (F.) (Chalcididae).…”
Section: Discussionmentioning
confidence: 99%